2012
DOI: 10.5792/ksrr.2012.24.3.137
|View full text |Cite
|
Sign up to set email alerts
|

The Tips and Pitfalls of Meniscus Allograft Transplantation

Abstract: When faced with an irrepairable meniscus or a patient who has had a total or subtotal meniscectomy, meniscus allograft transplantation (MAT) is the preferred modality to restore biomechanical function of the meniscus. The indications for meniscus allograft transplantation are yet to be established. However, currently, MAT has previously been indicated for symptomatic patients who have mild or early osteoarthritis, are younger than 50 years of age, and present with an Outerbridge grade II or lower. The short- t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
72
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 56 publications
0
72
0
3
Order By: Relevance
“…partial meniscectomy and saucerization) or transplant a whole meniscus in the form of a size-matched allograft [5,9]. Optimal management for this condition is controversial given the upfront cost differential between the two treatment options: the more expensive meniscal allograft transplantation compared with standard partial meniscectomy.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…partial meniscectomy and saucerization) or transplant a whole meniscus in the form of a size-matched allograft [5,9]. Optimal management for this condition is controversial given the upfront cost differential between the two treatment options: the more expensive meniscal allograft transplantation compared with standard partial meniscectomy.…”
Section: Introductionmentioning
confidence: 98%
“…Optimal management for this condition is controversial given the upfront cost differential between the two treatment options: the more expensive meniscal allograft transplantation compared with standard partial meniscectomy. The goal of meniscal allograft is to relieve pain, improve function, and slow the progression of osteoarthritis [2,3,9,10]. The indications for meniscal allograft are controversial, but typically include age <50 years without significant arthritic changes, normal alignment, and normal ligamentous stability [4,9].…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al 203 , in a systematic review, evaluated 38 studies with 1,056 allografts, concluded that MAT reduces the progression of osteoarthritis, although it is unlikely to be as effective as the native meniscus. Some long-term follow-up studies showed that the technique resulted in graft degeneration, deformation, and tear, and structural changes in the remodeling process in early meniscus transplantation @ C I C E d i z i o n i I n t e r n a z i o n a l i cases, disrupting functional restoration of the original meniscus 204 . In a meta-analysis study, Meredith et al 205 indicated that extensive resections and females had the highest correlations with radiographic evidence of OA, and in a follow-up study of 328 unstable knees, the best correlation with the severity of OA was the time that had elapsed since meniscectomy.…”
Section: Results Of Meniscal Transplantsmentioning
confidence: 99%
“…Noyes et al observed a different timing of graft failure in the lateral (mean of 53 months) and medial (mean of 25 months) menisci [34]. The most common complications for MAT are: graft tear, graft shrinkage, graft extrusion, knee stiffness (especially if MAT with associated procedures), infection, immune reaction, suture granulomas, portal pain, synovitis, and intraarticular hematoma [6,7,13,16,35,36]. The rate of graft tear is approximately 8% [6], which may be treated conservatively or operatively with meniscal repair or meniscectomy [18,37].…”
Section: Complicationsmentioning
confidence: 99%